Does Baseline Severity of Arm Pain Influence Outcomes Following Single-Level Anterior Cervical Discectomy and Fusion? - Patel, Madhav R.; Jacob, Kevin C.; Chavez, Frank A.; Parsons, Alexander W.; Vanjani, Nisheka N.; Pawlowski, Hanna; Prabhu, Michael C.; Singh, Kern (Asian spine journal, 2023)
Study Design: Retrospective cohort.Purpose: To assess preoperative arm pain severity influence on postoperative patient-reported outcomes measures (PROMs) and minimal clinically important difference (MCID) achievement following single-level anterior cervical discectomy and fusion (ACDF).Overview of Literature: There is evidence that preoperative symptom severity can affect postoperative outcomes. Few have evaluated this association between preoperative arm pain severity and postoperative PROMs and MCID achievement following ACDF.Methods: Individuals undergoing single-level ACDF were identified. Patients were grouped by preoperative Visual Analog Scale (VAS) arm ≤8 vs. >8. PROMs collected preoperatively and postoperatively included VAS-arm/VAS-neck/Neck Disability Index (NDI)/12-item Short Form (SF-12) Physical Composite Score (PCS)/SF-12 mental composite score (MCS)/Patient-Reported Outcomes Measurement Information System physical function (PROMIS-PF). Demographics, PROMs, and MCID rates were compared between cohorts.Results: A total of 128 patients were included. The VAS arm ≤8 cohort significantly improved for all PROMs excepting VAS arm at 1-year/2-years, SF-12 MCS at 12-weeks/1-year/2-years, and SF-12 PCS/PROMIS-PF at 6-weeks, only (p ≤0.021, all). The VAS arm >8 cohort significantly improved for VAS neck at all timepoints, VAS arm from 6-weeks to 1-year, NDI from 6-weeks to 6-months, and SF-12 MCS/PROMIS-PF at 6-months (p ≤0.038, all). Postoperatively, the VAS arm >8 cohort had higher VAS-neck (6 weeks/6 months), VAS-arm (12 weeks/6 months), NDI (6 weeks/6 months), lower SF-12 MCS (6 weeks/6 months), SF-12 PCS (6 months), and PROMISPF (12 weeks/6 months) (p ≤0.038, all). MCID achievement rates were higher among the VAS arm >8 cohort for the VAS-arm at 6-weeks/12-weeks/1-year/overall and NDI at 2 years (p ≤0.038, all).Conclusions: Significance in PROM score differences between VAS arm ≤8 vs. >8 generally dissipated at the 1-year and 2-year timepoint, although higher preoperative arm pain patients suffered from worse pain, disability, and mental/physical function scores. Furthermore, clinically meaningful rates of improvement were similar throughout the vast majority of timepoints for all PROMs studied.